2000
DOI: 10.1507/endocrj.47.197
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid-Stimulating Antibody in a Patient with Euthyroid Graves' Disease.

Abstract: Abstract.We report an 11-year-old girl with euthyroid Graves' disease. She was referred to our clinic because of left exophthalmos without other symptoms suggestive of hyperthyroidism. Her serum concentration of free thyroxine (FT4) and free triiodothyronine (FT3) were normal, but thyroid-stimulating hormone (TSH) was below normal and impaired TSH response to TSH releasing hormone (TRH) was found. Although the sera were positive for anti-TSH receptor antibody (TRAb) and thyroid-stimulating antibody (TSAb), bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…Though the pathogenesis of infiltrative ophthalmopathy is still unresolved, it has been suggested that autoantibodies to an antigen cross-reacting with the TSH receptor may be involved [18]. Watanabe et al reported the relationship between TSAb activity and severity of ophthalmopathy [19].…”
Section: Discussionmentioning
confidence: 99%
“…Though the pathogenesis of infiltrative ophthalmopathy is still unresolved, it has been suggested that autoantibodies to an antigen cross-reacting with the TSH receptor may be involved [18]. Watanabe et al reported the relationship between TSAb activity and severity of ophthalmopathy [19].…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Because most cases involving euthyroid TAO showed no thyroid abnormalities except testing positive for thyroidstimulating hormone receptor antibodies (TRAbs), 7,9 the clinical significance of TRAb as a criterion in the diagnosis of euthyroid TAO has been suggested. 3,6 Recently, Eckstein et al 10 reported that the TRAb titer was low in euthryoid and hypothyroid patients, suggesting that a more sensitive assay technique was necessary to utilize the TRAb assay for diagnosis of euthyroid/hypothyroid TAO.…”
Section: Introductionmentioning
confidence: 99%